Вплив технічно-естетичних показників якості паковання на попит продукції - Калініна, Олена; Байцар, Роман (Видавництво Львівської політехніки, 2016)
Розглянуто вплив естетичних показників якості паковання на конкурентоспроможність товарів і їх просування на споживчому ринку, значення низки чинників у формуванні художньо-естетичної складової паковання, а також чинні нормативні документи, які регламентують стандарти на паковання. Рассмотрено влияние эстетических показателей качества упаковки на конкурентоспособность товаров и их продвижение на потребительском рынке, значение ряда факторов для формирования художественно-эстетической составляющей упаковки, а также существующие нормативные документы, регламентирующие стандарты на упаковку. Demand for consumer goods is quite difficult socio-economic category. In the decision to purchase a particular product objectively influenced by factors such as the usefulness of product, price and income of buyer. Appearance of packaging, largely must to help shoppers navigate in the ocean products, introduces him to the principal advantage of goods and helps to make the right choice. Packing regarded as artistic and functional complex that includes three interrelated components: the material and constructive, communicative and informative and artistically shaped. Along with certain characteristics that a quality modern packaging must have , such as environmental friendliness, reliability, lightness, ease of use, portability, possibility of recycling, the expressive aesthetic appearance is prerequisite for competitiveness. When creating attractive, positive for consumer visual "picture" of packaging should take into account certain characteristics of consumer audience. Unconditional and unquestionable influence on visual perception packaging design has national mentality and traditional features, characteristic of the population of a country and certain stereotypes in the perception of the visual image. Yes, always negative impact on demand of commodity will have colors, symbols and signs on the packaging, which historically perceived negatively by citizens of the country, and, conversely, the positive experience of the people, their traditions cause positive emotions, to encourage purchases. For example, in the Middle East blue color associated with mourning, but in Europe it is called royal, red symbolizes the loss in Turkey, while in China it is perceived as a symbol of goodness and joy Age of consumers affects visual perception packaging and hence on the demand of goods too. Thus, the packaging products for children should be attractive for them to have a bright, saturated colors, pleasant to the touch surface. For packaging of goods for teenagers would be appropriate concise, accurate slogans slang phrases, positive characters which common in subculture of teenagers. Brand designers must also take into account the objective gender differences in the perception of packaging for men and women. Also physiological characteristics of men and women directly displayed on differences in purchasing behavior. Color, size, shape of packaging "female" goods traditionally associated with elegance, beauty and charm of women, while the visual image of the "male" goods must emphasize poise, courage, determination of man. So, the shape of the male deodorant "24/7" has restrained rectangular silhouette and a bottle designed for women mimics the configurati of female body. When developing packaging designs undeniable influence on his visual image has a price equivalent of product which this packaging has positioned . Dear goods require of expensive, high-quality, sometimes of exclusive means of its representation. Packaging of luxury goods should speak eloquently about his status. Today designers and marketers to attract buyers are use innovative, increasingly expressive and creative packaging solutions of visual image, using innovative and sometimes extraordinary general idea. Containers used for packaging products must comply with the current standards or specifications and provide storage and immutability of their properties during the warranty period. Type of packaging determined by current regulations. Ukraine's WTO membership and ratification of the Association Agreement between Ukraine and the EU obliges Ukraine to the implementation of international standards governing the modern requirements for packaging consumer products.
Keywords: характеристики паковання; дизайн паковання; споживчий попит; стандарти; характеристики упаковки; дизайн упаковки; потребительский спрос; стандарты; characteristics of packaging; packaging design; consumer demand; standards; 006:658.8